2011
DOI: 10.1111/j.1750-2659.2011.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a household randomized controlled trial of hand washing and face masks to reduce influenza transmission in Bangkok, Thailand

Abstract: Please cite this paper as: Simmerman et al. (2011) Findings from a household randomized controlled trial of hand washing and face masks to reduce influenza transmission in Bangkok, Thailand. Influenza and Other Respiratory Viruses 5(4), 256–267 Background  Evidence is needed on the effectiveness of non‐pharmaceutical interventions (NPIs) to reduce influenza transmission. Methodology  We studied NPIs in households with a febrile, influenza‐positive child. Households were randomized to control, hand washing (HW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
219
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(228 citation statements)
references
References 26 publications
2
219
3
3
Order By: Relevance
“…The threat of pandemic A/H5N1 influenza and resultant pandemic planning drove the first RCTs of facemasks in various settings. [7][8][9][10][11][12][13][14][15][16][17][18][19] The aim of this review is to inform policy makers and stakeholders by examining and summarising the available evidence related to the efficacy of facemasks and respirators, current practice, and guidelines, as well as highlighting the gaps in evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The threat of pandemic A/H5N1 influenza and resultant pandemic planning drove the first RCTs of facemasks in various settings. [7][8][9][10][11][12][13][14][15][16][17][18][19] The aim of this review is to inform policy makers and stakeholders by examining and summarising the available evidence related to the efficacy of facemasks and respirators, current practice, and guidelines, as well as highlighting the gaps in evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Masks in community settings have no clearly proved efficacy (9)(10)(11)(12)(13)(14). In three trials, participants were randomized either to hand washing or to hand washing plus surgical masks (9,11,13), with no clear additional benefit of masks.…”
Section: Introductionmentioning
confidence: 99%
“…In three trials, participants were randomized either to hand washing or to hand washing plus surgical masks (9,11,13), with no clear additional benefit of masks. We have previously shown that masks in compliant users in the household setting reduced the risk of influenza-like illness (ILI) (12).…”
Section: Introductionmentioning
confidence: 99%
“…Several community-based observational and intervention studies have attempted to evaluate the transmission and control of seasonal influenza, assessing both pharmaceutical and non-pharmaceutical interventions (6)(7)(8)(9). Despite the understanding gained from these studies, additional longitudinal epidemiological studies are required to assess the spread of influenza virus (10).…”
Section: Introductionmentioning
confidence: 99%